The Venture Bros. Season one [videorecording (DVD)] - McCulloch, Chris; Urbaniak, James, 1963-; Sinterniklaas, Michael; Warburton, Patrick (Distributed by Warner Home Video, 2006)
Dr. Venture is a failed super-scientist living in the shadow of his legendary father. His twin sons Hank and Dean are just two pie-eyed obstacles between him and what's left of his dreams.